2011
DOI: 10.1102/1470-7330.2011.0009
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression of combined hepatocellular carcinoma and cholangiocarcinoma

Abstract: Combined hepatocellular carcinoma-cholangiocarcinoma (cHCC-CC) is a rare entity comprising 1–14.2% of all primary liver carcinomas. In this report, we present a case of rapid progression of cHCC-CC, a rare tumor in a 77-year-old Caucasian male patient with hepatitis B-induced cirrhosis, moderately elevated alpha fetoprotein, and imaging and pathologic features of a mixed liver tumor. There was no evidence of metastatic disease in the chest, abdomen or pelvis by computed tomography (CT) scan at the time of diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…We found that intratumor necrosis was an independent predictor for CHC, not consistent with the published papers (14)(15)(16)(17)(18)(19)(20)(21), conclusions of which were also inconsistent. We suggest two explanations of why radiographic imaging of CHC varies among researches.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We found that intratumor necrosis was an independent predictor for CHC, not consistent with the published papers (14)(15)(16)(17)(18)(19)(20)(21), conclusions of which were also inconsistent. We suggest two explanations of why radiographic imaging of CHC varies among researches.…”
Section: Discussioncontrasting
confidence: 86%
“…Additionally, radiographic imaging plays a vital role in the diagnosis and differential diagnosis of liver tumors. However, CHC can share some similar radiographic characteristics with ICC (15,16), so it is challenging to differentiate diagnosis preoperatively through those methods (17). For example, there have been some studies regarding CHC's radiographic characteristics (18)(19)(20)(21)(22)(23)(24)(25), but these studies' results are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…One published case report describes rapid progression of a confirmed hepatocholangiocarcinoma after ablation. 21 These tumors are less vascular and more fibrotic than pure HCC and it has been suggested that this renders them less likely to respond to TACE. 22…”
Section: Pathologic Assessmentmentioning
confidence: 99%
“…Some authors had proposed that CHCC-C behaves like HCC, but in fact a biliary cell component is now thought to confer a poorer prognosis (Wu et al 1996), and CHCC-C can undergo rapid progression (Saboo et al 2011;Garancini et al 2014;Kim et al 2014) In a study on 25 patients, the overall median survival of CHCC-C patients was 38 weeks while that of HCC patients was 54 weeks (Chantajitr et al 2006). In 29 Korean patients with CHCC-C who underwent liver resection or liver transplantation, diseasefree survival rates at 6 months, 1 year, and 3 years were 51.1 %, 38.3 %, and 25.6 %, respectively.…”
Section: Biology Of Diseasementioning
confidence: 99%